Specific Aspects of Children's Anemia - Sobirova Nargiza Ravshanbek kizi (Zien Journals, 2023)
This article presents the main classification and differential diagnostic schemes of anemia. The emphasis in diagnosis is on laboratory tests that form the basis of differential diagnosis and differentiated treatment of anemia in children.
Keywords: anemia; differential diagnosis; diagnostic algorithm